Nonsurgical treatment of periapical lesion associated with type III dens invaginatus using calcium hydroxide: A case report - Kalaskar R; Kalaskar A (Wolters Kluwer Medknow Publications, 2008)
Dens invaginatus is a developmental malformation of teeth, probably resulting from an infolding of the papilla during tooth development. It predisposes the tooth to develop caries and periapical pathosis. Root canal therapy may present many problems because of the complex anatomy of the teeth. The purpose of this case report is to describe the endodontic treatment of an Oehlers type III dens invaginatus that perforated into the apical area. Calcium hydroxide powder mixed with normal saline, was used as an intracanal medicament. This eradicated the pathogenic microorganisms in the invagination and preserved the vitality of the tooth, allowing gutta-percha obturation in the invagination.